5^6x-1 = 25, but I'm not sure how they got it:
5^6x-1 = 5^2
6x-1 = 2
6x = 3
x = 0.5
How did they get from 5^6x-1 = 5^2 to 6x-1 = 2?
Thanks!How does this work? (Indices)?
log(x^y) base x = y
so log(5^x) base 5 = x.
In most cases, if you do (or undo) any operation on both sides of the equation, nothing really changes.How does this work? (Indices)?
a^m=a^n
implies that m=n
it's a formula
so u already know that 5^2 is 25.therefore,they equated 6x-1 and 2.simple reason!!!
Ask yourself this question,
4^(2) = 4^(x)
What must x be for the equation to hold true?
x = 2 right, because 4^(2) = 4^(2).
Same applies with a slightly more complicated equation.
5^(6x - 1) = 5^2
6x - 1 = 2
x = 1/2
Plug in x = 1/2,
5^(6*(1/2) - 1) = 5^2
5^(3 - 1) = 5^2
5^2 = 5^2 of course.
So generally, it's good to know that
If (m)^x = (m)^y, then x = y.
hope i was of help.
when the bases are the same, then the powers can be compared. that is why you can equate the indices.
so .. if you have something like 3^x = 9, we can say that 3^x=3^2, thus x=2
5^6x-1 = 5^2
a^b=a^c
b log(a)=c log(a)
the log(a) cancels
so b=c
or 6x-1=2
No comments:
Post a Comment